Peran Manajemen Perpustakaan Sekolah terhadap Pengembangan Minat Baca Siswa: Studi Kasus di SMAN 4 Batanghari - Istikomatul Kiroma (JMiE (Journal of Management in Education), 2023)
The research aims to examine the level of students' reading interest and the implementation of library management in efforts to enhance the literacy culture in schools. The results of the study indicate that the library plays a central role in supporting the development of students' potential, particularly through the creation of a conducive literacy atmosphere. However, library management at SMAN 4 Batanghari still faces various challenges, such as limitations in infrastructure, a lack of competent human resources, and insufficient attention from the educational institution towards library development. To overcome these obstacles, the school has taken several strategic steps, including providing training for library managers, increasing the availability of library materials, and developing literacy services that can encourage both students' and teachers' reading interest. These findings affirm that effective library management is an important factor in fostering a sustainable reading culture within the school environment.